تغير القيم زمن جائحة كورونا -دراسة مقاصدية - قارش, جميلة; بروال, نسيمة (جامعة الوادي - University of Eloued, 2022)
تنطلق هذه الدراسة من واقعنا الفردي والجماعي المتغير في ظل جائحة كورونا التي غيّرت أولوياتنا ونمط حياتنا وعلاقاتنا، وأثرت تأثيرا بارزا على قيمنا الإسلامية بمختلف أنواعها وصورها؛ عقديا عباديا وأخلاقيا. وفي ظل هذا الجائحة التبست على الكثيرين المواقف والخيارات، خاصة مع الاضطرار لوقف كثير من الشعائر والعادات، كصلاة الجماعة في المسجد والحج، بعد فرض الحجر والتباعد الاجتماعي، وتضييق الحركة الاجتماعية والتجارية. وبعد تأسيس النظر في الموضوع، ببسط ما يتعلق بالقيم مفهوما وأنواعا، وبيان أهم عوامل تغير القيم، ومنها الظروف الطارئة كحال هذه الجائحة، ثم عرض مجموعة من القيم الإسلامية التي تغير مؤشرها بفعل الجائحة. وباستحضار مقاصد الشريعة الإسلامية، تتأسس رؤيتنا لهذه الجائحة، ويرتفع اللبس والتداخل الحاصل في تقدير المصالح والمفاسد فيما يتعلق بالوباء، لتنبني أحكامنا ومواقفنا من الخصائص الأساسية للمصلحة المعتبرة شرعا. مع استحضار المراتب الثلاث ؛ الضروريات والحاجيات والتحسينيات، والكليات المقاصدية الخمس: الدين والنفس والعقل والنسل والمال. هذه الثقافة المقاصدية الأصيلة، أثبتت جدارتها وأهليتها لتأطير واقعنا وتجاوز مشكلاتنا زمن الجائحة، ومن شأن ذلك تثمين الآثار الإيجابية لتغير القيم زمن كورنا، مع تجاوز الآثار السلبية وتقليصها ومحاصرتها. للوصول بالبشرية عامة، والأمة الإسلامية خاصة، إلى بر الأمان، لتتخلى عن غرورها وضلالها، وتعلن عجزها وضعفها، وتعود إلى ربها ودينها وشريعتها. This study is based on our changing individual and collective reality in light of the Corona pandemic, which changed our priorities, our lifestyle and our relationships, and had a significant impact on our Islamic values of all kinds and forms; Doctrinally and morally. In light of this pandemic, many attitudes and options were confused, especially with the need to stop many rituals and customs, such as congregational prayer in the mosque and Hajj, after imposing stone and social distancing, and narrowing social and commercial movement. After establishing the consideration of the subject, by extending what is related to values in terms of concepts and types, and clarifying the most important factors of changing values, including emergency conditions such as the case of this pandemic, then presenting a set of Islamic values whose index has changed due to the pandemic. By invoking the purposes of Islamic law,"maqassid" our vision for this pandemic is established, and the confusion and overlap in the assessment of interests and corruptions in relation to the epidemic increases, so that our judgments and positions are based on the basic characteristics of the legitimate interest. With the conjuration of the three ranks; The obligations, necessities and improvements, and the five intentional levels: religion, soul, mind, offspring and money. This authentic intentional culture has proven its worth and eligibility to frame our reality and overcome our problems in the time of the pandemic, and this will value the positive effects of changing values in the time of Corona, while overcoming, reducing and besieging the negative effects. To bring humanity in general, and the Islamic nation in particular, to safety, to abandon its arrogance and misguidance, and to declare its inability and weakness, and to return to its Lord, its religion and its law.
Values’ Change In Corona Pandemic Period - A Maquassid Study -
مقال
Keywords: القيم الإسلامية ; تغير القيم ; جائحة كورونا ; مقاصد الشريعة الإسلامية